Cross-border relationships in Europe - István Süli-Zakar; Gábor Lenkey (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2014)
Borders and border regions are special research fields of political geography and economic geography. Border is a term of several meanings as it is frequently used in philosophical, mathematical, geometrical, historical and geographical sense. In the present paper only political borders are considered and an outline regarding the political geographical and economic effects of European state borders is given. There are no bad or good borders only the political systems fill them with emotional content. Measures aiming to develop border areas and support for them are in the centre of European Union efforts.